The Impact of ApoE and FOXO3 Genotype on the Risk of Intracerebral Hemorrhage Among American Men of Japanese Ancestry. (17th December 2021) - Chen, Randi; Greenberg, Steven; Ross, G; Willcox, Bradley; Masaki, Kamal; Nakagawa, Kazuma
Abstract: This study assessed the impact of APOE e2, e4 minor alleles and the FOXO3 longevity-associated genotype (carrier of SNP rs2802292 "G" allele) on 34-year incidence of intracerebral hemorrhage (ICH). Cox regression models were performed to assess the impact of the APOE e2, e4 and FOXO3 G alleles on the incidence of ICH. A total of 6483 participants were eligible for the analyses. 213 participants developed ICH. Cox-regression model showed neither APOE minor allele vs. common genotype (APOE e3/e3: RR 0.89, 95% CI: 0.64-1.22, p=0.46) nor FOXO3 G carrier status (RR 0.97, 95% CI: 0.72-1.29, p=0.82) was associated with incident ICH. Conversely, both hypertension (RR: 1.46, 95% CI: 1.07-2.00, p=0.02) and low cholesterol level (RR: 0.99, 95% CI: 0.99-1.00, p=0.001) were associated with incident ICH. Carriage of APOE e2 or E4 alleles and the FOXO3 G allele do not appear to impact risk of ICH over 34 years in this cohort.